Self-prescription practices by Nigerian medical doctors - Joseph Fadare; Olufemi Desalu (South African Family Practice, 2014)
Background: Self-prescription by physicians is a form of self-care that has generated considerable controversy in recent years. The prevalence of self-prescription practices by physicians has been widely studied in North America, Europe and Asia. Few studies on physician self-prescribing and prescribing for family members have been carried out in Nigeria. The primary aim of this study was to investigate the prevalence of self-prescription by medical doctors in Nigeria.